2018
DOI: 10.1111/ap.12256
|View full text |Cite
|
Sign up to set email alerts
|

How Effective is Cognitive Remediation in Enhancing Vocational Outcomes for Job Seekers with Severe Mental Illness in Australia?

Abstract: Objective Despite advances in the treatment of people with severe mental illness (SMI), access to work for this community still remains a challenge. Cognitive remediation (CR) is an intervention that can improve employment outcomes, especially when offered alongside employment support. This pilot study aimed to determine whether CR enhances vocational outcomes for job seekers participating in an innovative vocationally oriented psycho‐educational program implemented in Australia. Method Fourteen participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Both the intervention group and control group improved over time, however there were no significant differences between groups on employment, clinical, or cognitive outcomes (42). Some other studies have indicated that cognitive remediation may be useful, but have not necessarily investigated its impact on job tenure (86,87).…”
Section: Cognitive Remediationmentioning
confidence: 91%
“…Both the intervention group and control group improved over time, however there were no significant differences between groups on employment, clinical, or cognitive outcomes (42). Some other studies have indicated that cognitive remediation may be useful, but have not necessarily investigated its impact on job tenure (86,87).…”
Section: Cognitive Remediationmentioning
confidence: 91%
“…Four of five studies that examined substance misuse reported significant reductions in participants' consumption of alcohol (Forbes et al 2012), tobacco (Baker et al 2006;Ashton et al 2015) and other drug use (Nagel et al 2009). Finally, four of seven studies found significant improvements in participants' psychosocial outcomes (Mueser et al 2006;Craigie and Nathan 2009;Nagel et al 2009;Contreras et al 2018). Nagel et al (2009) observed better overall psychosocial wellbeing among participants who received the CBT-based motivational interviewing therapy program than those who did not.…”
Section: Therapeutic Programsmentioning
confidence: 96%
“…The remaining four studies implemented different types of therapeutic models of care. Contreras et al (2018) examined cognitive remediation therapy, which involved cognitive skills training to provide individuals with the resources to improve their psychosocial outcomes (e.g. employment, social relationships).…”
Section: Therapeutic Programsmentioning
confidence: 99%
See 1 more Smart Citation